Identification of downstream target genes regulated by the nitric oxide–soluble guanylate cyclase–cyclic guanosine monophosphate signal pathway in pulmonary hypertension. (June 2016) - Zou, Lihui; Xu, Xiaomao; Zhai, Zhenguo; Yang, Ting; Jin, Junhua; Xiao, Fei; Wang, Chen
Objective: To investigate the downstream target genes regulated by the nitric oxide–soluble guanylate cyclase–cyclic guanosine monophosphate (NO-sGC-cGMP) signal pathway and their possible roles in the pathogenesis of pulmonary hypertension (PH). Methods: Digital gene expression tag profiling was performed to identify genes that are differentially expressed after activation of the NO-sGC-cGMP signal pathway in human pulmonary artery smooth muscles cells using 8-bromo-cyclic guanosine monophosphate, BAY 41-2272 and BAY 60-2770. Results were confirmed using real-time polymerase chain reaction. Gene ontology and signal transduction network analyses were also performed. Results: A number of genes were differentially expressed, including MMP1, SERPINB2, GREM1 and IL8 . A total of 68 gene ontology terms and seven pathways were found to be associated with these genes. Most of these genes are involved in cell proliferation, cell migration and apoptosis, which may contribute to the pathological pulmonary vascular remodelling in PH. Conclusion: These results may provide new insights into the molecular mechanisms of PH.